2003
DOI: 10.1152/japplphysiol.00502.2002
|View full text |Cite
|
Sign up to set email alerts
|

Speech movements do not scale by orofacial structure size

Abstract: The potential role of a size-scaling principle in orofacial movements for speech was examined by using between-group (adults vs. 5-yr-old children) as well as within-group correlational analyses. Movements of the lower lip and jaw were recorded during speech production, and anthropometric measures of orofacial structures were made. Adult women produced speech movements of equal amplitude and velocity to those of adult men. The children produced speech movement amplitudes equal to those of adults, but they had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…Thus, it is not possible to comment on possible correlations between the magnitude of oral articulatory movement and skeletal or morphological variations. However, a recently reported analysis of size scaling of oral movement in speech production failed to find significant evidence of a size-amplitude scaling relationship [62]. This evidence suggests that normal variations in craniofacial and oral articulatory size do not pose major concerns for interpretation of the present data.…”
Section: Limitationssupporting
confidence: 38%
“…Thus, it is not possible to comment on possible correlations between the magnitude of oral articulatory movement and skeletal or morphological variations. However, a recently reported analysis of size scaling of oral movement in speech production failed to find significant evidence of a size-amplitude scaling relationship [62]. This evidence suggests that normal variations in craniofacial and oral articulatory size do not pose major concerns for interpretation of the present data.…”
Section: Limitationssupporting
confidence: 38%
“…Additional analyses of parts of the present dataset as well as data from the other protocols are planned for submission in parallel as separate publications. At present, these separate reports involve the relationship between speech movements and orofacial structure size (Riely & Smith, 2003) and the independent control of each articulator (Walsh & Smith, 2002).…”
Section: Methods Participantsmentioning
confidence: 99%
“…This result is initially surprising, since young children, with their smaller oral structures, must be using more of the available articulatory space for their production of stressed syllables. However, prior evidence has shown that adults and children produce similar amplitude movements overall, even with their differences in structure size (Riely & Smith, 2003). Children may produce these ''hyperarticulated'' movements to achieve an acoustic goal.…”
Section: Developmental Changementioning
confidence: 96%